Assessment of Sweet Potato Ipomoea batatas (Lam.) Accessions for Resistance to Sweet Potato Feathery Mottle Virus - Boureima, SAKANDE; Moustapha, KOALA; Hamadou, SIDIBE; Koussao, SOME (Annual research & review in biology, 2025)
Sweet potato plays an important role in human and animal nutrition. In many parts of the world, it has been used as an emergency crop, enabling populations to survive difficult situations. Despite its adaptation to a variety of environments and growing conditions, sweet potato production is subject to a number of abiotic and biotic constraints, including viruses. Sweet potato feathery mottle induced by sweet potato feathery mottle virus (SPFMV) is one of the most damaging virus diseases of sweet potato (Ipomoea batatas). Genetic control is considered as very promising mean the control the disease. Microsatellite markers (SSR) were assessed for their possible use in marker assisted selection (MAS) of sweet potato for resistance to SPFMV. A collection of 86 sweet potato accessions and 131 F1 hybrids were evaluated for resistance to the virus by assessing the accumulation of viral particles by Enzyme-linked immunosorbent assay (ELISA). Up to 21.83% of the accessions and 29.8% of F1 hybrids showed resistance to the virus as they did not develop any symptom and ELISA failed to detect the virus in leaf samples. Assessment of SSR markers clustering structure and use of principal component analysis indicated that seven SSR markers were correlated to virus accumulation. Validation of these correlations should allow the use of these markers in MAS to improve sweet potato for resistance to SPFMV.